A second helping of gumbo for the soul : more liberating stories and memories to inspire females of color - Trotman Scott, Michelle Frazier; Walters, Nicole McZeal; Young, Jemimah L.; Ford, Donna Y. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"A Second Helping of Gumbo for the Soul is a collection of essays, stories, and narratives designed to inspire and empower women of color through the use of storytelling and narratives. This second edition is a sequel to the first Gumbo for the Soul and includes more..."-- Provided by publisher.
Keywords: African American women -- Social life and customs -- Anecdotes.; African American women -- Social conditions -- Anecdotes.; African American women -- Biography -- Anecdotes.; Conduct of life -- Anecdotes.; elektronické knihy; Anecdotes.; Biographies.; Social Science -- Women's Studies.; Ethnic studies.; Gender studies: women and girls.; electronic books